Globalization a reference handbook - Ervin, Justin; Smith, Zachary A. (Zachary Alden) 1953-.; Gale Group (Santa Barbara, Calif. ABC-CLIO, 2008)
Provides an introduction to the phenomenon of globalization and looks at its economic, environmental, and security dimensions as interpreted from different political points of view.
Background and history -- Problems, controversies, and solutions -- Special U.S. issues -- Chronology -- Biographical sketches -- Data and documents -- Directory of organizations -- Resources.
Electronic reproduction.
Keywords: Globalization -- Handbooks, manuals, etc; Globalization -- Economic aspects; Globalization -- Environmental aspects; Electronic books